CITIZEN JOURNALISM PRACTICE AND SOCIAL MEDIA USAGE DURING SOCIAL DARWINISM (#EndSARS) PROTEST AMONG YOUTHS IN LAGOS, NIGERIA - Rasheed, Buhari Olaoluwa (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
The study investigated social media usage for the popular #EndSARS protest that changed and shook the nation's landscape. Social Darwinist ideas was used to rationalize the marginalization of certain groups who may be seen as less capable or inferior. It explored the usage of social media that allowed the effective sharing of audio-visual messages by the #EndSARS protesters, especially the youths in Ikeja. 400 copies of questionnaire data were tested using simple percentages and presented in frequency distribution tables, the study concluded that youths use the media peculiar to them like social media for protest activities. The traditional media sought more objective ways to improve the reportage of events especially of national importance and concern to youths.